Dinamika Aktor dalam Persiapan Pemekaran Daerah Balanipa - Nurul Fibrianti (Magister Ilmu Politik Universitas Hasanuddin, 2017)
Expansion area is considered as an appropriate solution to accelerate development and increase regional prosperity. The research aims to describe and analysis the dynamics of among the actors of local politician in preparing the regional expanding of new autonomy of region of Balanipa. The writer used the concepts of decentralization and regional autonomy, concept of the formation of New Autonomy Regency (NAR), concept of elite theory and concept of conflict theory. The method used was qualitative and with analysis descriptive approach. The research was conducted in Polewali Mandar regency as a mother region. The data were collected with interview, field observation. Library Studi, then the data were analyzed and concluded with data reduction technique. The results indicate the occurence of dynamics between political actors take place in expansion preparation of regency candidate of Balanipa. Dynamics occurs at the level of the internal actor executives, legislative, public figures and between political actors. But behind the conflict eventually leads to a consensus (agreement) is to jointly agree on the existence of Balanipa expansion. The occurance of dynamics influenced by five factors i.e. historical factors of Balanipa, public welfare improvement, actors’ willing to be adopted as public figures, the interest to gain power and promise of the campaign prior to the election implementation.